Detection and analysis of dynamic patterns of diurnal expression of mammalian genes - O. V. Podkolodnaya; N. N. Tverdokhleb; N. L. Podkolodnyy (Вавиловский журнал генетики и селекции)
The purpose of the study is to identify and analyze patterns of the diurnal dynamics of the expression of genes that diﬀer in the shape of the curve. It can be expected that the similarity of the patterns of daily expression (shape of the curve) of genes is a reﬂection of the synchronization of gene expression by common external and internal signals or participation in similar biological processes. Diﬀerent signals that have daily dynamics (light, activity, nutrition, stress, temperature, etc.) can aﬀect diﬀerent levels of expression regulation, which can be manifested in various forms of patterns of daily gene expression. In our research, we used experimental data on gene expression at the level of translation (ribosome profling) in the liver and kidney of a mouse (GSE67305 and GSE81283). To identify genes with a daily rhythm of expression, we used a oneway analysis of variance. To identify similarinshape curves of the daily dynamics of gene expression, we propose an approach based on cluster analysis. The distance between the genes was calculated by aligning the phases and fnding the maximum crosscorrelation between the patterns of the daily expression of these genes by the cyclic shift. This approach allowed us to identify genes that have not only expression patterns with a single maximum (sinusoidal, asymmetrical, shifted to the left or right, pulsed), but also complex composite signals with several extremes. As a result, the groups of genes united by the similarity of the shape of the daily expression curve without regard to their phase characteristics were identifed. GO enrichment analysis of groups of genes with sharply different patterns of daily expression (sinusoidal and pulsed) in the mouse kidneys and liver showed that the group of genes with a sinusoidal pattern was more associated with regulation of circadian rhythm and metabolism. The group of genes with a pulsed pattern is largely associated with the protective functions of the organism, which require the quick response. Thus, our studies have confrmed the eﬀectiveness of the proposed approach to the analysis of the diurnal dynamics of gene expression. The identifed dynamic patterns of diurnal expression are important for the further study of complex circadian regulation, synchronization and interaction of biological processes with diurnal dynamics in mammals.